고준위 방사성폐기물의 국내철도운반에 관한 방사선영향 예비평가 - 서명환(Myunghwan Seo), 도호석(Hoseog Dho), 홍성욱(Sung-Wook Hong), 박진백(Jin Beak Park) (Journal of nuclear fuel cycle and waste technology (Online), 2017)
국내 원자력발전소의 사용후핵연료는 소내저장시설에 보관되어 있으나 저장시설의 용량 확장이 어려움이 있으며, 연구기관 의 연구로에서 발생하는 고준위 방사성폐기물도 자체 보관중이나 영구적으로 저장할 수 없다. 또한 원전의 해체 시에도 고 준위 방사성폐기물이 발생할 것으로 예상된다. 이에 따라, 본 연구에서는 현재 개발된 사용후핵연료 운반용기를 사용하여 고준위 방사성폐기물을 가상의 관리시설로 철도를 통하여 운반하는 경우에 대하여 작업자 및 운반경로 주변 일반인의 예상 피폭선량을 평가하였으며, 그 결과를 국내 법적기준치와 비교하였다. 또한, 고준위 방사성폐기물의 상하차 작업 시 작업자 와 운반용기 간 거리와 운반사고 시 방사성핵종의 누출율의 변화에 따른 피폭선량의 변화에 따른 피폭선량 추이와 운반에 사용되는 열차의 구성에 따른 운반작업자의 피폭선량 변화를 분석하였다. 본 연구에서 설정한 모든 조건에서의 예상피폭선 량은 국내 법적제한치 이하임을 확인하였다. In Korea, commercial nuclear power plants and research reactors have on-site storage systems for the spent nuclear fuel, but it is difficult to expand the facilities used for the storage systems. If decommissioning of nuclear power plants starts, an amount of high level radioactive waste will be generated. In this study, a radiological impact assessment of the railroad transport of high level radioactive waste was carried out considering radiation workers and the public, using the developed transport container as the transport package. The dose rates for workers and the public during the transport period were estimated, considering anticipated transport scenarios, and the results compared with the regulatory limit. A sensitivity analysis was also carried out by considering the different release ratios of the radioactive materials in the high level radioactive waste, and different distances between the transport container and workers during loading and unloading phases and while attaching another freight car. For all the anticipated transport scenarios, the radiological impacts for workers and the public met the regulatory limits.